Предмет: Математика,
автор: lambert1337
Решить уравнение
-(6x-1)^2+(4x+3)(4x-3)+18=0
Ответы
Автор ответа:
0
-(6x-1)^2+(4x+3)(4x-3)+18=0
(4x-3)(4x+3)-(6x-1)^2+18=0
-20x^2+12x+8=0
Решаем через Дискриминант:
a=-20;b=12;c=8
D=12^2-4*(-20)*8=784
x1=-2/5
x2=1
Ответ:-2/5 и 1
(4x-3)(4x+3)-(6x-1)^2+18=0
-20x^2+12x+8=0
Решаем через Дискриминант:
a=-20;b=12;c=8
D=12^2-4*(-20)*8=784
x1=-2/5
x2=1
Ответ:-2/5 и 1
Похожие вопросы
Предмет: Другие предметы,
автор: udaevvladimir83
Предмет: Математика,
автор: barboskinadasa12
Предмет: Английский язык,
автор: anutavideo
Предмет: История,
автор: Dangerous11111
Предмет: Математика,
автор: Серый3568